Comparison of methods in the diagnosis of Helicobacter pylori infection in Quindío, Colombia. (Colombia Medica, 2006)
Introduction: Helicobacter pylori is a gramnegative bacterium that colonizes the gastric mucosa, and infects more than half of the worldwide population, causing gastritis and ulcer-peptic disease and being associated with gastric carcinoma and gastric lymphoma (MALT). Objective: To compare the performance index of techniques of routine diagnosis and PCR in order to establish by case definition the prevalence of infection by H. pylori in patients with gastroduodenal disease in Quindío. Methodology: In 73 patients were taken six biopsies. One antral for the PCR-ureC, three for culture (antral, body and fundus), other antral for rapid urease test (RUT). The previous were united to one of the body for histological examination. The performance index was established for each of the methods. For definitive diagnosis of the infection we used the case definition (positive H pylori) was used: A patient was classified as H. pylori positive with isolation of bacteria in culture or based on the agreement of at least two positive tests (histological examination, RUT and PCR). Results: The histological examination was positive 79.5% (58/73) in antral biopsy and in body 82.2% (60/73) and the combination of both biopsies was 94.5% (69/73). Culture assessment in the three biopsies showed identical results, 75.4% (55/73) and by combination all biopsies were 86.3% (63/73). The RUT in antral biopsy was 79.5% (58/73) and for PCR-ureC of antral biopsy was 86.3% (63/73). The prevalence for H pylori infection was 97.3% (71/ 73) in accordance with the case definition. The comparison of the results of each method in front of the result by case definition, the histological examination, culture, PCR and RUT presented 2, 8, 8, and 13 false negative in their order and none presented false positives. Performance indexes (PI) for each method were: Culture, 78.1% with sensibility, 88.7%, and identical results in three biopsies. The RUT, had 82.2% and 81.7% of sensibility. The histological examination was 87.0% with 86.6% of sensibility in antral biopsy and 89.9% in body biopsy with sensibility of 90.9%. And PCR-ureC had 89.0% with sensibility, 88.7% The combination of the results for the three biopsies for culture increased their PI to 89.0% with sensibility of 88.7%. The combination of results of the two biopsies in the histological examination also showed PI increased of 97.3% with sensibility of 97.2% and showed significant differences in front of the other methods. Conclusion: For the definitive diagnosis of H pylori infection it should use the case definition concept which allows establishing the real prevalence of the infection being higher than detected by the individual methods. Additionally, if it is not possible to utilize the case definition concept, is recommended the histological examination in two biopsies (antral and body).